Persepsi Pembaca Terhadap Website Literacycloud Sebagai Alternatif Kegiatan Membaca - Anida Uswatun Hasanah; Levy Husnul Lailina; Najma Azzahro Aulia; Nida Adilah Rahmah; Nur Indah Septiani; Sofyan Iskandar; Neneng Sri Wulan; Nuur Wachid Abdul Majid (FKIP, Universitas Palangka Raya, 2023)
This research is motivated by the digital transformation and the massive use of technology in various fields. Education is no exception. For example, reading activities are generally carried out using physical books. Currently it can be done through a website called Literacycloud. This research, using a quantitative method by utilizing the System Usability Scale (SUS), aims to measure the level of usability of the Literacycloud website. Testing was carried out using the SUS questionnaire, which consisted of ten statements, and a Likert scale was used to determine respondents' responses. The test was conducted to evaluate the usability level of the Literacycloud website. Based on the results of this study, it was found that the Literacycloud website has a SUS value of 65.25 and is in the C letter rank and 36-64% percentile rank. Therefore, this Literacycloud website is not widely known